PENGELOLAAN POTENSI SUMBERDAYA KELAUTAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN NELAYAN (Studi Kasus Community-Based Management Wilayah Pesisir di Kabupaten Tuban) - Shofwan, -; Khusaini, Moh.; Badriyah, Nurul (Journal of Indonesian Applied Economics, 2008)
The  objectives  of  this  research  were  to  analyze Community-Based Managementapplication,  influence and  factors  to management of coastal resources especiallyincreasing fisherman income on 5 districts in sub-province Tuban. The results showedthere are extensive community participation, capacity building and village coastalmanagement  plans. These  plans  are  significant  in many  ways. Planning  is  alsounderway to scale-up from pilot sites to a provincial program that provides technicaland financial support services to village government and communities coast-wide.Keywords: Community-Based Management, Coastal Resources,  Coastal  Village,Fisherman Income